THE IMPLEMENTATION OF PBX (PASSIVE BOX) IN TEACHING PASSIVE VOICE - Rohmah, Vikit Fadila; Nugraha, Laurentius Elyas (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2017)
According to the English teachers of SMAN 1 Kudus especially those who teach the eleventh graders, learning passive voice becomes hard for students when they need to transform the active into passive voice because they are stuck in the formula of passive voice in different tenses. This study aims to find out the significant difference between the group who learns using PBX (Passive Box) and that who learns without using PBX (Passive Box). This study uses true-experimental design. The experimental group is asked to learn passive voice uses video and PBX (Passive Box) while the control group only uses video. To know the result of the study, the gathered data in post-test are computed using Independent Sample t-test in SPSS where the result can be seen from the Levene’s Test. The result shows that PBX (Passive Box) is effective for students to learn passive voice. Therefore, PBX (Passive Box) can be used as an additional medium in learning passive voice for Senior High School students.